2019
DOI: 10.21831/ltr.v18i1.21992
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Inheritance System of the Gambang Rancag Oral Tradition in the Betawi Community

Abstract: STRUCTURE, FUNCTION, AND INHERITANCE SYSTEM OF THE GAMBANG RANCAG   ORAL TRADITION IN THE BETAWI COMMUNITYAbstractJakarta is inhabited by people formed from a melting plot process, namely mixing of various ethnicities and regions, both from within and outside Indonesia. From the melting plot process, the position of the Betawi people changed to a new identity called the Betawi tribe or the Betawi people. This aims of study is to describe the structure, function, and inheritance sistem of the gambang rancag   o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The meaning of essential words in data ( 17), ( 18), and (19) will not provide a complete message to the reader without paying attention to the pattern of sentence construction, the structure of the text contained within, and even the context within the text (Attas, 2019).…”
Section: (20) Kopi: Lembut Nian Usai Diperammentioning
confidence: 99%
“…The meaning of essential words in data ( 17), ( 18), and (19) will not provide a complete message to the reader without paying attention to the pattern of sentence construction, the structure of the text contained within, and even the context within the text (Attas, 2019).…”
Section: (20) Kopi: Lembut Nian Usai Diperammentioning
confidence: 99%
“…The negation function shows resistance or rebellion or changing the prevailing norms (Attas, 2019). Can be seen from the fragment of the story when Patih Durjaman suggested that marriage with Pangeran Sabang of Madusari be carried out.…”
Section: The Function Of Negationmentioning
confidence: 99%